Pengaruh Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar Siswa Kelas X di SMK Negeri 1 Bitung - Febriola Cecilia Sigar; Gilly M. Tiwow; Feine R. Tulung (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study aims to determine the effect of the Problem-Based Learning (PBL) model on student learning outcomes in Vocational Basics subjects in grade X MPLB students at SMK Negeri 1 Bitung. The background of this study is based on the students' tendency to be passive in the learning process and their low critical thinking and problem-solving skills, due to the continued dominance of conventional learning methods in the classroom. Based on interviews with homeroom teachers, it was discovered that students were not accustomed to actively engaging in discussions and problem-solving. This study was a quantitative study with a quasi-experimental design using a non-equivalent control group design. The sample consisted of two classes: an experimental class taught using the PBL model and a control class taught using the conventional model. The research instruments consisted of 15 multiple-choice pre-test and post-test items. Data were analyzed using normality tests, homogeneity tests, and hypothesis tests (t-test and Mann-Whitney U). The results showed a significant difference between student learning outcomes in the experimental and control classes. Students who participate in PBL learning achieve higher learning outcomes than those taught conventionally. Therefore, it can be concluded that the Problem-Based Learning model has a positive effect on student learning outcomes in Vocational Basics.